Moral costs, the informal sector and unemployment - Ann-Sofie Kolm; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2001)
While examining the macroeconomic effects of increased government control of the informal sector, this paper develops a two-sector general equilibrium model featuring matching frictions and worker-firm wage bargaining. The same good is produced in the formal and in the informal sector. Moral considerations are determinant for whether the worker search for jobs in the formal or in the informal sector. We analyse the impact of higher punishment fees and a higher audit rate on wages, sector division, unemployment and welfare.
hdl:10398/7525
Keywords: E20; E24; 330; Employment; Unemployment; Wages; Macroeconomics